PROGNOSTIC PARAMETERS FOR THE RECOVERY OF RENAL FUNCTION IN PATIENTS WITH OBSTRUCTIVE UROPATHY - Bundu, Aristo; Danarto, H R (Indonesian Journal of Urology, 2018)
Objective: The aim of this study was to determine the prognostic parameters for the recovery of renal function in patients with obstructive uropathy after the release of obstruction. Material & methods: This is a retrospective cohort study. Secondary data from the patient's medical record was used to determine whether the ratio of blood urea nitrogen (BUN)/creatinine, hemoglobin, hyperkalemia, blood glucose, renal parenchymal thickness, and obstruction etiology are prognostic parameters for recovery of renal function in patients with obstructive uropathy after release of obstruction. Bivariate was used to analyze the data using Chi-square and Fisher's exact test with significance level of p<0.05 to evaluate the significance. Results: Based on total of 66 research samples, it was found that renal parenchymal thickness was ≥10 mm (p=0.001), hemoglobin level was ≥10 mg/dL (p=0.001), and BUN/creatinine ratio was ≥10 (p=0.003), it had significant correlation with the recovery of renal function, meanwhile, obstruction etiology variable (p=0.566), and hyperkalemia (p=0.792) did not provide significant recovery of renal function. Conclusion: Renal parenchymal thickness, hemoglobin level, and BUN/Creatinin ratio are the prognostic parameters for recovery of renal function after release of obstruction.